Delays in Protecting a Small Endangered Cetacean: Lessons Learned for Science and Management - Slooten, Elisabeth; Dawson, Stephen M. (Frontiers in Marine Science, 2021)
Hector’s dolphin is a small, endangered dolphin species found exclusively in the inshore coastal waters of New Zealand. We draw on 36 years of involvement in research on Hector’s dolphin, and its subspecies Māui dolphin, to provide an overview of the species’ conservation biology, and summarise the incremental progress towards sustainable management. We offer lessons learned at the interface between science and management. These lessons emphasise the importance of acting early, having clear management goals and ensuring that the area over which protection measures are applied is sufficiently large to be biologically relevant. High-quality information is vital, but gaining appropriate conservation outcomes depends also on social and political processes. We warn that compromise can have high biological costs and that representation on stakeholder groups is usually biased towards extractive users and short-term economic perspectives. In New Zealand, outcomes have depended closely on politics; the greatest gains have been made when relevant government ministers took a special interest. Scientists have crucial roles in every phase of this process. Each country and each species will present their own challenges and opportunities. We trust, however, that lessons learned from Hector’s dolphin conservation will be useful to researchers and managers elsewhere.